2005
DOI: 10.1179/174328105x15896
|View full text |Cite
|
Sign up to set email alerts
|

Development of stepwise thermal model for annealing line heating furnace

Abstract: Knowledge of the steel strip temperature throughout the length of the annealing line continuous heating furnaces is important to guarantee the physical properties of the metal produced. Given that online temperature measurement is difficult, a stepwise model has been developed that considers the furnace as being divided up into enclosures. This model is easy to implement and has a short run time. The steel strip is considered to be subject to convection and radiation mechanisms, and surface and overall heat ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…The convective heat transfer coefficients h i are calculated using the Nusselt number. The same models of natural and forced convections as represented in the literature [4] are adopted in the present study. Expression (10), proposed by McAdams [12], is considered for the natural convection in the horizontal heated surfaces facing upwards, as in the ceiling of the chamber, to calculate the heat transfer losses to the surrounding furnace, and also for the cooled horizontal surfaces facing downwards, as in the ceiling of the chamber, to calculate the convective heat transfer rate.…”
Section: Temperature Of Strip In Preheating Furnace 259mentioning
confidence: 99%
See 2 more Smart Citations
“…The convective heat transfer coefficients h i are calculated using the Nusselt number. The same models of natural and forced convections as represented in the literature [4] are adopted in the present study. Expression (10), proposed by McAdams [12], is considered for the natural convection in the horizontal heated surfaces facing upwards, as in the ceiling of the chamber, to calculate the heat transfer losses to the surrounding furnace, and also for the cooled horizontal surfaces facing downwards, as in the ceiling of the chamber, to calculate the convective heat transfer rate.…”
Section: Temperature Of Strip In Preheating Furnace 259mentioning
confidence: 99%
“…The temperatures of the atmosphere at each zone are also assumed to be distributed Table 2. Properties of atmosphere [4] Property Function Range q, kg=m 325.38=T 400 < T(K) < 1000 c p , J=kg  K 1.096  10 À4 T 2 þ 5.499  10 À2 T þ 1054.84 400 < T(K) < 1000 k, W=m  K 6.358  10 À5 T þ 1.299  10 À2 400 < T(K) < 1000 m, Pa  s 2.966  10 À8 T þ 1.011  10 À5 400 < T(K) < 1000 uniformly. They generally can be measured by experiment.…”
Section: Preheating Furnacementioning
confidence: 99%
See 1 more Smart Citation
“…In their models, the effect of convective cooling on the strip was introduced via a constant heat transfer coefficient. Prieto et al [4,5] developed a powerful stepwise thermal model for annealing line. In their model the furnace was divided into several enclosures in which overall heat balances were conducted.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, importance is being given to the modelling of the behaviour of the steel strip in order to improve the control of the annealing process in an HDGL. Thus, in Prieto et al [5] a stepwise mathematical model is reported that allows determining the temperature of the strip based on both its and the furnace's mathematical characterisation, and which considers the phenomena of conduction, convection and radiation existing in the furnace and also present between it and the steel strip.…”
Section: Control Of the Annealing Process For The Steel Stripmentioning
confidence: 99%